2018
DOI: 10.1371/journal.pone.0195470
|View full text |Cite
|
Sign up to set email alerts
|

Is empathy one of the Big Three? Identifying its role in a dual-process model of ideology and blatant and subtle prejudice

Abstract: In the field of the social psychology of prejudice, John Duckitt's Dual-Process Cognitive-Motivational Model of Ideology and Prejudice has gained a firm grounding over the past decade and a half, while empathy has become one of the most powerful predictors of prejudice, alongside right-wing authoritarianism and social dominance orientation. This study integrates empathy into the dual-process model, exploring the effects of this variable, along with the impact of personality and ideological attitudes, on prejud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…However, in the positive emotional dimension (i.e., sympathy), we found that participants reported the highest possibility of feeling sympathy for the COVID-19 patients (vs. the patients with all other diseases we measured). Although studies have documented a negative association between compassion and stigma ( Batson et al, 1997 ; Galinsky and Moskowitz, 2000 ; Stark et al, 2013 ; Boag and Carnelley, 2016 ; Álvarez-Castillo et al, 2018 ; van Bommel et al, 2021 ). The public’s sympathy for people associated with the pandemic disease might be crucial to the development of stigmatization interventions in future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the positive emotional dimension (i.e., sympathy), we found that participants reported the highest possibility of feeling sympathy for the COVID-19 patients (vs. the patients with all other diseases we measured). Although studies have documented a negative association between compassion and stigma ( Batson et al, 1997 ; Galinsky and Moskowitz, 2000 ; Stark et al, 2013 ; Boag and Carnelley, 2016 ; Álvarez-Castillo et al, 2018 ; van Bommel et al, 2021 ). The public’s sympathy for people associated with the pandemic disease might be crucial to the development of stigmatization interventions in future research.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only four studies have examined the link between trait empathy and outgroup attitudes, with two studies including parallel empathy. Álvarez-Castillo et al (2018) found that outgroup prejudice was related to a combination of cognitive and affective empathy components among adults. However, this relation was indirect and mediated by social dominance orientation, i.e.…”
Section: Empathy and Intergroup Attitudesmentioning
confidence: 99%
“…Considerably fewer studies, however, have focused on individual differences in trait empathy, that is the general tendency to empathize with other persons (rather than outgroup members in particular), and particularly little is known about the impact of these differences on children's outgroup attitudes. The few studies that did focus on trait empathy indicate that the tendency to empathize with others relates to more outgroup positivity in children (Nesdale et al, 2005), adolescents (Miklikowska, 2018), and adults (Álvarez-Castillo, Fernández-Caminero & González-González, 2018).…”
mentioning
confidence: 99%
“…Based on theoretical studies of the variables that affect prejudice and empirical studies on transnational Islamic groups' characteristics, several variables are assumed to affect group prejudices; first, intergroup contact. This affects prejudice because theoretically, the intensity of contact can increase understanding of other groups and reduce stereotypes and the illusion of outgroup homogeneity (Álvarez-Castillo et al, 2018;Pettigrew, 1997). Intergroup contacts are assumed to affect the prejudice of transnational Islamic groups (especially Jama'ah Tabligh) because the activity that is emphasized, and which is the main task of each member of the group, is to preach to all mankind across groups, religions, ethnicities, and nations.…”
Section: │ 171mentioning
confidence: 99%
“…Several studies have shown that intergroup prejudice is caused by the lack of individual contact between groups (Abrams, 2010;Abrams & Hogg, 1999;Allport, 2004;Álvarez-Castillo et al, 2018;R. Brown, 1995;Pettigrew, 1998;Rutland et al, 2010).…”
Section: │ 171mentioning
confidence: 99%